COMMENTS ON 'THE ACCRETION CONCEPT OF INCOME' - Corbin, Donald A. (The Accounting Review, 1963)
The article comments on a manuscript "The Accretion Concept of Income," by professor G. Edward Phillips. The Philips article demonstrates quite well that progress in accounting theory should begin with developing a single income concept, rather than a variety of income concepts, and that this single income concept should also aid various interested parties in making a variety of decisions. His point that simply because accountants must supply varied data for many different uses, does not imply a need for more than one concept of income is well taken. He says, agreement on a meaningful concept of income is essential to improvement of the financial reporting function of accountants, and there is no inherent reason for this concept to interfere with the collection, analysis and interpretation of data relevant to particular decisions. Philips does not ignore the price-level problem in his paper, but concludes that even a severe inflation or deflation would not necessitate eliminating unreal gains or losses from income statements. He also states that his suggested accretion concept eliminates the bunching effect of realizing periodic accretion gains all at one time, as is presently done.